An improved method for tight integration of GPS and strong-motion records: Complementary advantages. Issue 11 (1st December 2015) - Tu, Rui; Zhang, Qin; Wang, Li; Liu, Zhanke; Huang, Guanwen
Abstract: The complementary nature of GPS and seismic sensors for station ground motion estimation is well recognized and many studies have proposed the integrated processing of the two datasets for obtaining more accurate and reliable seismic waves (displacement, velocity and acceleration). There are two critical issues in the integrated processing; one is the precise correction of the strong-motion's baseline shifts which are caused by tilting and/or rotation of the seismic sensors, the other is the suitable constraint of the high resolution accelerations to get more reliable seismic waves. In this contribution, we present an improved approach for the integration estimation in two steps. First, proper introduction of the baseline-corrected acceleration into the Precise Point Positioning (PPP)'s state equation and treatment of the baseline shifts as unknown parameters to be estimated for each epoch. Second, after correction of these baseline shifts, use of the high resolution acceleration for constraint of the GPS solution and ambiguity resolution. The efficiency of the improved approach was validated using an experimental dataset which was recorded by a pair of collocated GPS antenna and an accelerometer, and it shows that the advantages of each sensor are complementary.